Improving efficiency through consolidation of jurisdictions? Evidence from the Cantons of Switzerland - Philippe K. Widmer; George Elias; Peter Zweifel (University of Zurich, Department of Economics, 2012)
The purpose of this paper is to analyze the optimal scale of local jurisdictions (cantons) in Switzerland applying Data Envelopment Analysis (DEA) to the years 2000 to 2004. Aggregate output performance indicators for four local government activities (administration, education, health, and transportation) are used to measure technical and scale efficiency and to derive DEA scores. Results show that these public services fail to exhibit economies of scale, undermining quests for centralization of public good provision while suggesting the possibility of Tiebout competition.
Keywords: C14; C67; H11; H72; H83; 330; DEA; efficiency measurement; economies of scale; public good provision; Switzerland; Gerichtsbarkeit; Verwaltungsreform; Skalenertrag; Öffentliche Güter; Data-Envelopment-Analyse; Teilstaat; Schweiz